Distribution and Habitat Suitability of Ross Seals in a Warming Ocean - Mia Wege (Frontiers in Marine Science, 2021)
Understanding the determinants of poorly studied species’ spatial ecology is fundamental to understanding climate change impacts on those species and how to effectively prioritise their conservation. Ross seals (Ommatophoca rossii) are the least studied of the Antarctic pinnipeds with a limited knowledge of their spatial ecology. We present the largest tracking study for this species to date, create the first habitat models, and discuss the potential impacts of climate change on their preferred habitat and the implications for conservation. We combined newly collected satellite tracking data (2016–2019: n = 11) with previously published data (2001: n = 8) from the Weddell, King Haakon VII and Lazarev seas, Antarctica, and used 16 remotely sensed environmental variables to model Ross seal habitat suitability by means of boosted regression trees for summer and winter, respectively. Five of the top environmental predictors were relevant in both summer and winter (sea-surface temperature, distance to the ice edge, ice concentration standard deviation, mixed-layer depth, and sea-surface height anomalies). Ross seals preferred to forage in waters ranging between −1 and 2°C, where the mixed-layer depth was shallower in summer and deeper in winter, where current speeds were slower, and away from the ice edge in the open ocean. Receding ice edge and shoaling of the mixed layer induced by climate change may reduce swimming distances and diving depths, thereby reducing foraging costs. However, predicted increased current speeds and sea-surface temperatures may reduce habitat suitability in these regions. We suggest that the response of Ross seals to climate change will be regionally specific, their future success will ultimately depend on how their prey responds to regional climate effects and their own behavioural plasticity.